MINIMASI DOWNTIME TOOL PUNCH MESIN HEADING PADA PREVENTIVE MAINTENANCE DENGAN METODE AGE REPLACEMENT - Santoso, Edi; Chairul, Edwin Julianto (Industrial and Systems Engineering Assessment Journal (INASEA), 2007)
Production machines can be a barrier for the on time product availability. If there is no time consideration of the usage of production machines or less in maintenance, the machines will not be used in product processing. In the case of tool punch Heading machine in which the machine need to maintain in the right period of time using Age Replacement method. This method can help management to determine the period in inspection and preventive maintenance. Based on time period, preventive maintenance that was done can be decrease downtime, increase machines availability and reliability.